Sociality shock - Šumi, Irena (Anthropological notebooks, 2025)
This paper reconsiders the epistemological foundations of anthropological theory by re-interpreting fieldwork not as a site of data collection, but as a condition of radical exposure and transformation. Drawing on both classical and contemporary sources from Malinowski’s Diary to recent work on affect and embodiment, it argues that the true origin of anthropological theorizing lies not in cultural observation per se, but in the fieldworker’s disorientation, estrangement, and social isolation. The term sociality shock is introduced to replace the misnomer “culture shock,” emphasizing that what the novice anthropologist experiences is not primarily cognitive or cultural, but affective and relational: the temporary loss of social intelligibility and existential anchoring in an unfamiliar social world. Far from being incidental, this vulnerable state becomes the engine of theoretical production. Against the backdrop of postmodern reflexivity and the politics of representation, the paper critiques earlier paradigms that framed fieldwork as either an objective science or a self-reflective narrative, arguing instead for a model of fieldwork as a structured epistemological ordeal. Drawing from phenomenology, postcolonial critique, and field-based testimonies, it proposes that theory emerges through embodied confrontation through the anthropologist’s gradual re-entry into sociality under novel terms, and the rebuilding of perspective from a position of self-induced social blindness. The argument culminates in a call to re-imagine fieldwork training and ethnographic pedagogy: not as a matter of mastering methods, but of preparing the ethnographer for dislocation, affective rupture, and epistemic reconstruction. Ultimately, this work reclaims theory not as a product of analytical distance, but as the outcome of having been undone and remade in the field.
Keywords: anthropological training; antropološko usposabljanje; družbenostni šok; epistemologija; epistemology; ethnographic pedagogy; etnografska pedagogika; fieldwork; sociality shock; terensko delo; utelešena produkcija znanja